Digital control design for single-phase matrix converter (SPMC) as a cycloconverter - Ab. Aziz, Norhafizawati (2007)
This report will focused on to design digital control for Single Phase Matrix Converter (SPMC) to operating as a cycloconverter. In this project, PIC and Xilinx FPGA were used to improve the digital control. The input for PIC will be come from Modulation Index circuit and Voltage Sensor circuit. This PIC will convert the voltage sensor output which is in sinusoidal signal into square wave signal. As long as the output from Modulation Index circuit is already in digital form so this PIC doesn't do any complicated function, it just moved the data from the input to output port. The output from PIC will interface with Xilinx Board to create SPWM. This modulation index data were used to adjust the amplitude of sinusoidal wave which is created inside Xilinx as needed before it will compared with triangular waveform also created inside Xilinx. After the comparison it will create Single Pulse Width Modulation (SPWM). This SPWM is useful to drive gating circuit. The output from voltage sensor will ensure that the output from Xilinx FPGA is synchronous with the frequency of the single phase output voltage. Then the state selector will determine and implement the operation of required switching state. The output will be check on the oscilloscope.